A Dive into Membrane Dynamics with Sponge Peptides. Issue 5 (21st May 2015) - Luo, Danmeng; Luesch, Hendrik
Abstract : In this issue of Chemistry & Biology, Arita et al. (2015) report that theonellamides can specifically recognize cholesterol in liquid-disordered environment, modulate membrane order, and change cell morphology and thus may serve as probes to unveil the enigmatic nature of cell membranes.